The survival effect of prolactin on PC3 prostate cancer cells. - Ruffion, A; Al-Sakkaf, K; Brown, B; Eaton, C; Hamdy, F; Dobson, P (2003)
OBJECTIVES: Recent studies suggest a paracrine/autocrine loop involving prolactin (PRL) within the human prostate. The aims of this study were to determine the effects of PRL on the growth and survival of prostate cancer cells and the intracellular signalling mechanisms underlying such effects. METHODS: The effect of PRL on proliferation of LNCaP, PC3 and DU145 was assessed by Coulter counting. The effect of PRL on TRAIL-, staurosporine- and flavopiridol-induced apoptosis was assessed by Timelapse microscopy and Annexin V binding. The status of the PRL receptor (PRL-R) and Akt/PKB (protein kinase B) activity were assessed by Western blotting. RESULTS: All three cell lines expressed both the short and long forms of the PRL receptor. Although, no significant effect of PRL on the proliferation of these cells was found, PRL partially inhibited TRAIL-induced apoptosis in PC3 cells. PRL also enhanced the phosphorylation of Akt/PKB in these cells. CONCLUSIONS: PRL had no significant effect on the proliferation of PC3, DU145 and LNCaP, but inhibited TRAIL-induced apoptosis in PC3 cells, possibly via enhanced Akt/PKB phosphorylation in PC3 cells. Further investigations are underway to determine the survival effect of PRL on the other two prostate cancer cell line.